Mesoporous carbon material as well as preparation method and application thereof

By developing mesoporous carbon materials with multi-stage pore structures, the problems of high cost and limited performance of silicon-carbon composite materials in the prior art have been solved, and high-performance and low-cost electrode materials are realized, which are suitable for lithium-ion batteries and other applications.

CN119551653APending Publication Date: 2025-03-04SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411732724.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The resin microporous carbon and biomass microporous carbon materials used in existing silicon-carbon composite materials have high cost, complex preparation process, and have limitations in electrical conductivity and structural stability, making it difficult to meet the needs of large-scale commercial production.

Method used

A mesoporous carbon material is developed with a multi-stage pore structure including macropores, mesoporous and micropores to form a three-dimensional network structure. Through the mixed in situ carbonization reaction of polymer materials, surfactants, inorganic salts and MOFs materials and carbon precursors, a "core-shell" structure is formed, and the mass transfer path and energy storage sites are optimized.

Benefits of technology

It improves the conductivity, energy storage capacity, mechanical strength and cycle stability of mesoporous carbon materials, reduces production costs, and is suitable for lithium-ion batteries and other energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160673300000091
    Figure BDA0005160673300000091
  • Figure BDA0005160673300000111
    Figure BDA0005160673300000111
Patent Text Reader

Abstract

The invention provides a mesoporous carbon material as well as a preparation method and application thereof. The mesoporous carbon material has a multi-stage pore structure, the multi-stage pore structure comprises macropores with the pore diameter larger than thousands of 50 nm, mesopores with the pore diameter of 2-50 nm and micropores with the pore diameter smaller than thousands of 2 nm, and the macropores, the mesopores and the micropores are communicated with one another to form a three-dimensional network structure; the mesopores and the micropores are distributed on the pore walls of the macropores, the mesopores accounting for more than 70% of the total number of the mesopores are distributed in a first area of the mesoporous carbon material, the micropores accounting for more than 80% of the total number of the micropores are distributed in a second area of the mesoporous carbon material, and the first area wraps the second area. The mesoporous carbon material provided by the invention is beneficial to thousand rapid ion transmission, has good conductivity and energy storage capacity, and is suitable for being applied to the fields of thousand secondary batteries, catalysts or adsorbents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to a mesoporous carbon material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electronic devices, the demand for high-performance electrode materials is growing. As a promising electrode material, silicon-carbon composites have attracted much attention due to their high specific capacity and good cycle stability. However, the resin microporous carbon and biomass microporous carbon materials commonly used in silicon-carbon deposition technology have the problem of high cost, which seriously restricts their promotion in large-scale commercial applications.

[0003] In the prior art, although resin microporous carbon and biomass microporous carbon materials have good pore structure and specific surface area, their preparation process is complicated, the raw material cost is high, and the output is limited. These factors make the final product expensive and difficult to meet the needs of large-scale commercial production. In addition, these traditional microporous carbon materials also have certain limitations in conductivity and structural stability, which affects the overall performance of silicon-carbon composites.

[0004] In order to solve the above problems, it is urgent to develop a new, low-cost, high-performance mesoporous carbon material to replace traditional resin microporous carbon and biomass microporous carbon materials. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide a mesoporous carbon material, wherein the mesoporous carbon material has a multi-level pore structure, wherein the multi-level pore structure includes macropores with a pore size greater than 50 nm, mesopores with a pore size of 2 to 50 nm, and micropores with a pore size less than 2 nm, wherein the macropores, mesopores, and micropores are interconnected to form a three-dimensional network structure;

[0007] The mesopores and micropores are distributed on the pore walls of the macropores, the mesopores accounting for more than 70% of the total number of mesopores are distributed in the first region of the mesoporous carbon material, and the micropores accounting for more than 80% of the total number of micropores are distributed in the second region of the mesoporous carbon material, and the first region wraps the second region.

[0008] The mesoporous carbon material provided by the present invention has a multi-level pore structure, with macropores as the main channels, and mesopores and micropores are formed on the pore walls of the macropores. The formed three-dimensional porous network structure can accelerate the transmission of electrolyte and ion diffusion; and the mesopores are mainly distributed in the shell region of the mesoporous carbon material, and the micropores are mainly distributed in the interior of the mesoporous carbon material. The mesopores in the shell region are conducive to rapid ion transmission, and the micropores in the core region can provide a large number of energy storage sites, thereby improving the conductivity and energy storage capacity of the mesoporous carbon material.

[0009] In some embodiments, the diameter of the mesoporous carbon material is 5 to 20 μm, the first region is a region 0 to 1.5 μm away from the surface of the mesoporous carbon material, and the second region is a region greater than 1.5 μm away from the surface of the mesoporous carbon material.

[0010] In some embodiments, the total pore volume of all pores in the mesoporous carbon material is 1.5 to 3.0 cm 3 / g, wherein the ratio of the total pore volume of all macropores, the total pore volume of all mesopores and the total pore volume of all micropores is (1-4):(4-7):(2-3), preferably (1.5-3.5):(4.5-6.1):(2-2.7).

[0011] In some embodiments, the specific surface area of ​​the mesoporous carbon material is 1500-2500 m 2 / g.

[0012] In some embodiments, the mesoporous carbon material is doped with 1-5 wt% of nitrogen. Doping with nitrogen can improve the electron conductivity of the mesoporous carbon material.

[0013] In some embodiments, the multi-level pore structure has a honeycomb structure, which includes regularly arranged hexagonal holes. This structure helps to optimize the connectivity of the internal pores, maximize the specific surface area and porosity of the material, thereby improving the fluidity and ion conduction efficiency of the electrolyte while maintaining good mechanical strength and structural stability. In addition, the efficient space utilization of the structure can significantly improve the energy density and power density performance of the material in the energy storage device; the honeycomb porous structure can also effectively mitigate volume changes, improve cycle stability, and provide lasting performance guarantees for electrochemical applications.

[0014] A second object of the present invention is to provide a method for preparing a mesoporous carbon material, comprising:

[0015] Under inert atmosphere conditions, pre-treating a mixed slurry containing a carbon precursor, MOFs, a surfactant, an inorganic salt and a polymer material at 120-150° C. to crystallize the MOFs in the mixed slurry and cross-link the MOFs with the carbon precursor and the polymer material;

[0016] subjecting the pretreated mixed slurry to an in-situ carbonization reaction to obtain an intermediate material;

[0017] The intermediate material is spray-dried to obtain a mesoporous carbon material.

[0018] In the preparation method, inorganic salts are used as hard templates to form macropores with a pore size greater than 50 nm during the in-situ carbonization process, surfactants are used as soft templates to form mesopores with a pore size of 2 to 50 nm during the in-situ carbonization process, and MOFs are carbonized and decomposed during the in-situ carbonization process to form micropores with a pore size less than 2 nm. Since inorganic salts have the strongest etching ability, they first form macropores on the surface of the carbon precursor; then, the surfactant will bind to the active sites of the macropore wall, synergistically with the inorganic salt, alleviate the etching ability of the inorganic salt, and thus etch out mesopores; and the MOFs material is initially wrapped by the polymer material and located inside the carbon precursor, and is gradually exposed and decomposed after the macropores and mesopores are formed to form micropores. The mesopores in the mesoporous carbon material prepared in this way are mainly distributed in the outer shell region of the mesoporous carbon material, and the generated micropores are mainly distributed in the inner shell region of the mesoporous carbon material, thus forming a "core-shell" structure, which is beneficial to improve the specific surface area and porosity of the material, optimize the mass transfer path, enhance the catalytic activity, and improve the electrolyte permeability and ion conductivity in energy storage applications.

[0019] In some embodiments, the in-situ carbonization reaction specifically includes: under inert atmosphere conditions, at a heating rate of 2 to 5°C / min, first raising the temperature to 300 to 500°C and keeping it warm for 1 to 2 hours, then raising the temperature to 500 to 700°C and keeping it warm for 1 to 2 hours, and then raising the temperature to 700 to 1000°C and keeping it warm for 2 to 4 hours.

[0020] In some embodiments, the inlet temperature of the spray drying is 180-300°C, the middle section temperature is 120-200°C, the outlet temperature is 60-100°C, and the spray drying time is 30-120min. The spray drying of the present invention preferably adopts three-stage temperature control, which is more conducive to further regulating the pore size distribution and increasing the specific surface area compared to single temperature control, thereby obtaining a material with better performance. The prepared mesoporous carbon material has a larger specific surface area, rich mesoporous structure, good conductivity and mechanical strength.

[0021] In some embodiments, the pretreatment time is 2 to 4 hours. The pretreatment process can promote the crystallization of MOFs materials, so that they form a complete and uniform crystal structure, which helps to form a more regular porous structure; the pretreatment process promotes the cross-linking between ZIF-8 and carbon precursors and polymer materials (such as PVP), which helps to form a more stable three-dimensional network structure and improve the mechanical strength and stability of the final product; during the pretreatment process, the interaction between the components begins to form a preliminary pore structure, laying the foundation for the subsequent carbonization process.

[0022] In some embodiments, the content of MOFs in the mixed slurry is 2-10wt% of the carbon precursor, the content of surfactant is 1-5wt% of the carbon precursor, the content of inorganic salt is 5-20wt% of the carbon precursor, and the content of polymer material is 10-30wt% of the carbon precursor.

[0023] In some embodiments, the MOFs include one or a combination of ZIF-8, MOF-5, MIL-88B(Fe) or HKUST-1.

[0024] In some preferred embodiments, the MOFs include ZIF-8. ZIF-8 can not only generate micropores during the in-situ carbonization and decomposition process to form a porous carbon structure with a high specific surface area, but also nitrogen-dope the mesoporous carbon material at the same time to improve the conductivity, structural stability and silicon affinity of the material. In addition, ZIF-8 can form a honeycomb structure containing hexagonal holes, because ZIF-8 is a metal organic framework material with a SOD topological structure and has a regular hexagonal symmetry. The hexagonal symmetry of ZIF-8 provides a template for directional growth of the surrounding carbon material during the decomposition process, guiding the carbon material to form a regular hexagonal hole structure.

[0025] In some embodiments, the carbon precursor includes one or a combination of carbon black, graphene, carbon nanotubes, activated carbon or mesocarbon microbeads.

[0026] In some preferred embodiments, the carbon precursor includes carbon black, graphene, carbon nanotubes, activated carbon and mesophase carbon microspheres. The various carbon precursors contained can interact with each other during the carbonization process to form a more stable three-dimensional conductive network structure to improve the conductivity and structural stability of the carbon material. Among them, carbon black as a basic carbon source can serve as a supporting skeleton for other carbon precursors; graphene has a two-dimensional layered structure and excellent conductivity, and can form crosslinks with other carbon precursors during the carbonization process to increase the conductive channel of the material; carbon nanotubes have a one-dimensional tubular structure, which can act as a conductive bridge during the carbonization process, connecting different carbon particles and improving the overall conductivity; activated carbon has a rich pore structure, which can increase the specific surface area of ​​the carbon material and provide attachment sites for other carbon precursors; mesophase carbon microspheres have a unique spherical structure and good graphitization ability, which can form a local ordered structure during the carbonization process to improve the structural stability of the carbon material. During the carbonization process, these carbon precursors of different forms interact through van der Waals forces and π-π stacking to form a tightly connected three-dimensional network structure. Carbon black and activated carbon provide the basic skeleton, graphene and carbon nanotubes form conductive channels, and mesophase carbon microspheres increase the local order. The result of this multi-component synergy is the formation of a carbon material with high conductivity, large specific surface area and good structural stability.

[0027] In some embodiments, the carbon precursor includes carbon black, graphene, carbon nanotubes, activated carbon and mesophase carbon microspheres with a particle size distribution in the range of 20 to 300 nm. That is, the present invention uses a combination of carbon precursors with a wider particle size distribution to construct a more stable three-dimensional conductive network structure and improve the conductivity and structural stability of the carbon material.

[0028] In some preferred embodiments, the carbon precursor includes 20-40 wt% carbon black, 10-30 wt% graphene, 5-15 wt% carbon nanotubes, 10-30 wt% activated carbon and 5-25 wt% mesocarbon microspheres.

[0029] In some embodiments, the polymer material includes polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polystyrene (PS), polymethyl methacrylate (PMMA), polyethylene glycol (PEG), polyvinyl pyridine (PVPy), polyacrylonitrile (PAN), polyamide (PA), polyethylene (PE), polypropylene (PP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethyleneimine (PEI), polysulfone (PSF), polyethersulfone (PES), polylactic acid (PLA), polycaprolactone (PCL), chitosan, cellulose and its derivatives or polyethylene oxide (PEO) One or more combinations thereof.

[0030] In some embodiments, the surfactant includes sodium dodecyl sulfate, but is not limited thereto.

[0031] In some embodiments, the inorganic salt includes sodium chloride, but is not limited thereto.

[0032] In some embodiments, the preparation method further comprises: introducing a nitrogen-containing atmosphere during the in-situ carbonization reaction to nitrogen-dope the mesoporous carbon material.

[0033] In some embodiments, the nitrogen-containing atmosphere is nitrogen gas and / or ammonia gas.

[0034] In some embodiments, the flow rate of the nitrogen-containing atmosphere is 50-200 mL / min.

[0035] In some embodiments, the preparation method further comprises post-processing the obtained mesoporous carbon material, wherein the post-processing comprises heat treatment and / or acid washing.

[0036] In some embodiments, the heat treatment is performed at a temperature of 300 to 500° C. and for a time of 1 to 3 hours.

[0037] In some embodiments, the acid washing includes: washing the mesoporous carbon material with a 1-3 mol / L acid solution to remove impurity ions therein.

[0038] The third object of the present invention is to provide a mesoporous carbon material prepared by any of the methods described above.

[0039] A fourth object of the present invention is to provide the use of the mesoporous carbon material in energy storage, catalyst preparation or adsorbent preparation.

[0040] In some preferred embodiments, the energy storage includes preparing a silicon-carbon composite material for a lithium-ion battery, a lithium-ion battery negative electrode, or a lithium-ion battery.

[0041] In some embodiments, the application includes: depositing silicon particles on the mesoporous carbon material to form a silicon-carbon composite material. The silicon-carbon composite material can be used as a negative electrode active material for a lithium-ion battery to prepare a lithium-ion battery negative electrode or a lithium-ion battery. Since the mesoporous carbon material has a large specific surface area, rich mesoporous structure, good conductivity and mechanical strength, as well as excellent adsorption performance and cycle stability, the formed silicon-carbon composite material has good overall conductivity, so that the lithium-ion battery prepared therefrom has good rate performance, cycle stability and capacity retention rate. Compared with the silicon-carbon composite materials in the prior art, the silicon-carbon composite materials prepared using the mesoporous carbon material of the present invention have significantly improved electrochemical performance and structural stability. The method for depositing silicon particles on the mesoporous carbon material can adopt any method for preparing silicon-carbon composite materials in the prior art, such as vapor deposition method, etc., and the present invention does not impose any particular restrictions on this.

[0042] In some embodiments, the application includes: using the mesoporous carbon material as a catalyst carrier to prepare a catalyst or directly using it as a catalyst. Specifically, metal or metal oxide nanoparticles can be loaded onto the mesoporous carbon material to prepare a composite catalyst. For example, precious metal nanoparticles such as platinum, palladium, and gold can be loaded onto mesoporous carbon materials for catalytic hydrogenation, dehydrogenation and other reactions; or transition metals such as iron, cobalt, and nickel or their oxides can be loaded onto mesoporous carbon materials for electrocatalysis, photocatalysis and other fields. In addition, the mesoporous carbon material itself can also be directly used as a carbon-based catalyst and applied to certain organic reactions or electrocatalytic reactions.

[0043] In some embodiments, the application includes: preparing an adsorption material using the mesoporous carbon material. For example, the surface of the mesoporous carbon material is subjected to functionalization treatments such as oxidation, amination, sulfonation, etc. by chemical modification to enhance its adsorption capacity for specific substances. The adsorption material can be used to adsorb various substances in gas, liquid or solid, such as organic pollutants, heavy metal ions, dye molecules, etc. Specifically, it can be applied to environmental management fields such as wastewater treatment, air purification, gas separation, oil-water separation, as well as biomedical fields such as drug delivery and molecular screening.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The mesoporous carbon material provided by the present invention has a multi-level pore structure, with macropores as the main channel, and mesopores and micropores are formed on the pore walls of the macropores. The formed three-dimensional porous network structure can accelerate the transmission of electrolyte and ion diffusion. The macropore main channel provides faster ion transmission and effectively reduces internal resistance; the mesopores are mainly distributed in the outer shell area of ​​the mesoporous carbon material, providing good mechanical buffering capacity as a buffer layer and further accelerating ion transmission; the micropores are mainly distributed inside the mesoporous carbon material, providing a large number of energy storage sites, thereby improving its conductivity and energy storage capacity; and the capillary effect produced by the synergistic effect of the mesopores and micropores can promote the penetration and retention of the electrolyte and improve the uniformity of the electrochemical reaction.

[0046] (2) The present invention utilizes polymer materials, surfactants, inorganic salts and MOFs materials mixed with carbon precursors to perform in-situ carbonization reaction to form a multi-level porous structure. The generated mesopores are mainly distributed in the outer shell region of the mesoporous carbon material, and the micropores are mainly distributed in the inner shell region of the mesoporous carbon material, thereby forming a "core-shell" structure;

[0047] (3) The mesoporous carbon material provided by the present invention is used to prepare the silicon-carbon negative electrode material for lithium-ion batteries. Since the mesoporous structure is conducive to the uniform distribution and fixation of silicon nanoparticles, and the microporous structure can provide a large number of lithium ion storage sites, it can significantly improve the cycle performance and rate performance of lithium-ion batteries. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0049] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available. The carbon black used in the specific embodiments of the present invention is purchased from Cabot Corporation, graphene is purchased from Sixth Element Materials Technology Co., Ltd., carbon nanotubes are purchased from Tiannai Technology Co., Ltd., activated carbon is purchased from Noliya Chemical Co., Ltd., and mesophase microspheres are purchased from Beijing Carbon Century Technology Co., Ltd.

[0050] Example 1

[0051] Embodiment 1 provides a mesoporous carbon material and a preparation method thereof, which specifically comprises the following steps:

[0052] Preparation of ZIF-8: Dissolve zinc nitrate in methanol to prepare a 0.2 mol / L zinc nitrate solution; dissolve 2-methylimidazole in methanol to prepare a 0.2 mol / L 2-methylimidazole solution, mix the zinc nitrate solution and the 2-methylimidazole solution in a volume ratio of 1:2, and stir at room temperature for 2 hours to form ZIF-8;

[0053] Weigh a carbon precursor, wherein the carbon precursor is prepared according to a raw material ratio of 30 wt% carbon black, 20 wt% graphene, 10 wt% carbon nanotubes, 25 wt% activated carbon and 15 wt% mesophase carbon microspheres;

[0054] The carbon precursor, polyvinyl pyrrolidone (PVP), sodium dodecyl sulfate (SDS), NaCl, ZIF-8 and deionized water are mixed to form a slurry, wherein the PVP content is 10wt% of the carbon precursor, the SDS content is 3wt% of the carbon precursor, the NaCl content is 10wt% of the carbon precursor, and the ZIF-8 content is 5wt% of the carbon precursor; under a nitrogen atmosphere, the temperature of the slurry is raised to 120° C. for pretreatment for 2 hours to promote the crystallization of ZIF-8 therein and cross-linking with the carbon precursor and PVP;

[0055] The pretreated slurry was placed in a tubular furnace and programmed to heat up at a rate of 2°C / min from room temperature to 400°C and kept at that temperature for 2 hours under a nitrogen atmosphere, then the temperature was raised to 600°C and kept at that temperature for 1 hour, and finally the temperature was raised to 850°C and kept at that temperature for 4 hours to perform in-situ carbonization to obtain an intermediate material;

[0056] After the intermediate material was cooled naturally, it was washed with 0.1 mol / L hydrochloric acid to remove residual metal ions and dried in vacuum at 80 °C for 12 h;

[0057] The washed intermediate material is then spray dried using multi-stage temperature control with an inlet temperature of 270°C, a middle section temperature of 180°C, and an outlet temperature of 90°C for 60 minutes to obtain a mesoporous carbon material.

[0058] Example 2

[0059] Embodiment 2 provides a mesoporous carbon material and a preparation method thereof, which specifically comprises the following steps:

[0060] Preparation of ZIF-8: Dissolve zinc nitrate in methanol to prepare a 0.5 mol / L zinc nitrate solution; dissolve 2-methylimidazole in methanol to prepare a 1.0 mol / L 2-methylimidazole solution, mix the zinc nitrate solution and the 2-methylimidazole solution in a volume ratio of 1:2, and stir at room temperature for 4 hours to form ZIF-8;

[0061] Weigh a carbon precursor, wherein the carbon precursor is prepared according to a raw material ratio of 35 wt% carbon black, 15 wt% graphene, 8 wt% carbon nanotubes, 22 wt% activated carbon and 20 wt% mesophase carbon microspheres;

[0062] The carbon precursor, PVP, SDS, NaCl, ZIF-8 and deionized water are mixed to prepare a slurry, wherein the PVP content is 20wt% of the carbon precursor, the SDS content is 1wt% of the carbon precursor, the NaCl content is 20wt% of the carbon precursor, and the ZIF-8 content is 2wt% of the carbon precursor; under a nitrogen atmosphere, the temperature of the slurry is raised to 150° C. for pretreatment for 4 hours to promote the crystallization of ZIF-8 therein and cross-linking with the carbon precursor and PVP;

[0063] The pretreated slurry is placed in a tube furnace and programmed to heat up at a rate of 5°C / min from room temperature to 500°C and keep the temperature for 1 hour, then the temperature is increased to 700°C and kept the temperature for 1 hour, and then the temperature is increased to 1000°C and kept the temperature for 2 hours to perform in-situ carbonization to obtain an intermediate material;

[0064] After the intermediate material was cooled naturally, it was washed with 0.1 mol / L hydrochloric acid to remove residual metal ions and dried in vacuum at 80 °C for 12 h;

[0065] The washed intermediate material is then spray dried using multi-stage temperature control with an inlet temperature of 240°C, a middle section temperature of 150°C, and an outlet temperature of 70°C for 90 minutes to obtain a mesoporous carbon material.

[0066] Example 3

[0067] Example 3 provides a mesoporous carbon material and a preparation method thereof, which specifically comprises the following steps:

[0068] Preparation of ZIF-8: Dissolve zinc nitrate in methanol to prepare a 0.2 mol / L zinc nitrate solution; dissolve 2-methylimidazole in methanol to prepare a 0.2 mol / L 2-methylimidazole solution, mix the zinc nitrate solution and the 2-methylimidazole solution in a volume ratio of 1:2, and stir at room temperature for 2 hours to form ZIF-8;

[0069] Weigh a carbon precursor, wherein the carbon precursor is prepared according to a raw material ratio of 40 wt% carbon black, 10 wt% graphene, 5 wt% carbon nanotubes, 30 wt% activated carbon and 15 wt% mesophase carbon microspheres;

[0070] The carbon precursor, polyvinyl pyrrolidone (PVP), sodium dodecyl sulfate (SDS), NaCl, ZIF-8 and deionized water are mixed to prepare a slurry, wherein the PVP content is 30wt% of the carbon precursor, the SDS content is 5wt% of the carbon precursor, the NaCl content is 5wt% of the carbon precursor, and the ZIF-8 content is 10wt% of the carbon precursor; under a nitrogen atmosphere, the temperature of the slurry is raised to 130° C. for pretreatment for 3 hours to promote the crystallization of ZIF-8 therein and cross-linking with the carbon precursor and PVP;

[0071] The pretreated slurry was placed in a tubular furnace and programmed to heat up at a rate of 2°C / min from room temperature to 400°C and kept at that temperature for 1.5 h under a nitrogen atmosphere, then the temperature was raised to 600°C and kept at that temperature for 1.5 h, and finally the temperature was raised to 700°C and kept at that temperature for 3 h to perform in-situ carbonization to obtain an intermediate material;

[0072] After the intermediate material was cooled naturally, it was washed with 0.1 mol / L hydrochloric acid to remove residual metal ions and dried in vacuum at 80 °C for 12 h;

[0073] The washed intermediate material is then spray dried using multi-stage temperature control, with an inlet temperature of 300°C, a middle section temperature of 200°C, and an outlet temperature of 100°C for 60 minutes to obtain a mesoporous carbon material.

[0074] Example 4

[0075] Example 4 is basically the same as Example 1, except that the ZIF-8 in Example 1 is replaced by MOF-5 (chemical formula is Zn4O(BDC)3, where BDC is terephthalic acid), and the rest is implemented in the same way as Example 1.

[0076] Example 5

[0077] Example 5 is basically the same as Example 1, except that the ZIF-8 in Example 1 is replaced by MIL-88B(Fe) (chemical formula is Fe3O(BDC)3(H2O)2), and the rest is implemented in the same way as Example 1.

[0078] Example 6

[0079] Example 6 is basically the same as Example 1, except that the ZIF-8 in Example 1 is replaced by HKUST-1 (chemical formula is Cu3(BTC)2, wherein BTC is trimesic acid), and the rest is implemented in the same manner as Example 1.

[0080] Example 7

[0081] Example 7 is basically the same as Example 1, except that the spray drying step in Example 7 does not perform three-stage temperature control. The spray drying process of Example 7 is: inlet temperature is 270°C, outlet temperature is 90°C, and duration is 60 minutes.

[0082] Example 8

[0083] Example 8 is basically the same as Example 1, with the only difference being that the nitrogen atmosphere during the carbonization process is replaced with argon, that is, in Example 8, nitrogen is not introduced for nitrogen doping.

[0084] Example 9

[0085] Example 9 is substantially the same as Example 1, except that the carbon precursor used in Example 9 is 100 wt % carbon black, and the rest is implemented in the same manner as Example 1.

[0086] Example 10

[0087] Example 10 is substantially the same as Example 1, except that the carbon precursor used in Example 10 is 60 wt % carbon black and 40 wt % graphene, and the rest is implemented in the same manner as Example 1.

[0088] Embodiment 11

[0089] Example 11 is substantially the same as Example 1, except that the carbon precursor used in Example 11 is 40 wt % carbon black, 30 wt % graphene and 30 wt % carbon nanotubes.

[0090] Example 12

[0091] Example 12 is basically the same as Example 1, except that the carbon precursor used in Example 12 is 35wt% carbon black, 25wt% graphene, 20wt% carbon nanotubes and 20wt% activated carbon, and the rest is implemented in the same way as Example 1.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that the slurry of Comparative Example 1 does not contain ZIF-8, and the rest is the same as Example 1.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that the slurry of Comparative Example 2 does not contain SDS, and the rest is the same as Example 1.

[0096] Comparative Example 3

[0097] The difference between Comparative Example 3 and Example 1 is that the slurry of Comparative Example 3 does not contain NaCl, and the rest is implemented in the same way as Example 1.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 1 is that the slurry of Comparative Example 4 does not contain PVP, and the rest is implemented in the same manner as Example 1.

[0100] Comparative Example 5

[0101] The only difference between Comparative Example 5 and Example 1 is that, in Comparative Example 5, the slurry is not pretreated, and the slurry containing the same carbon precursor, PVP, SDS, NaCl and ZIF-8 as in Example 1 is directly carbonized, and the rest is implemented in the same way as in Example 1.

[0102] Table 1 Relevant structural characteristics of the mesoporous carbon materials prepared in the examples and comparative examples of the present invention

[0103]

[0104] The present invention also detects the pore distribution of the mesoporous carbon materials prepared in Examples 1 to 3 and Comparative Example 4, and finds that in Example 1, more than 83% of the mesopores are distributed in the region of 0 to 1.5 μm from the surface of the mesoporous carbon material, and more than 92% of the micropores are distributed in the region greater than 1.5 μm from the surface of the mesoporous carbon material. In Example 2, more than 85% of the mesopores are distributed in the region of 0 to 1.5 μm from the surface of the mesoporous carbon material, and more than 91% of the micropores are distributed in the region greater than 1.5 μm from the surface of the mesoporous carbon material. In Comparative Example 4, since the slurry does not contain the polymer material PVP, MOFs cannot be wrapped by PVP, and the micropores formed during the carbonization process tend to be uniformly formed on the macropore walls, and do not have the characteristics of being concentrated inside the carbon material.

[0105] In addition, by comparing Examples 1, 4, 5, and 6, it was found that when the MOFs material was ZIF-8, the prepared mesoporous carbon material had a honeycomb pore structure, that is, it contained regularly arranged hexagonal pores, indicating that the hexagonal symmetry of ZIF-8 provided a template for directional growth of the surrounding carbon material during the decomposition process, guiding the carbon material to form a regular hexagonal pore structure.

[0106] The mesoporous carbon material obtained in the above embodiment and comparative example is used to prepare a silicon-carbon composite material. The preparation method adopts a vapor deposition method, which specifically includes the following steps:

[0107] The pre-prepared mesoporous carbon material is surface activated and then placed on the sample holder of the vapor deposition equipment; under inert atmosphere conditions, the vapor deposition equipment is heated to a deposition temperature of 700°C; silane and carrier gas are introduced therein, with the silane gas flow rate being 3L / min, the carrier gas flow rate being 7L / min, and the deposition time being 8h, so as to deposit silicon particles on the mesoporous carbon material; the mesoporous carbon material containing silicon particles is annealed at a temperature of 800°C for 3h to obtain a silicon-carbon composite material.

[0108] The silicon-carbon composite material prepared above is used to prepare a lithium-ion battery, which specifically includes the following steps:

[0109] Take the silicon-carbon composite material prepared above, add 5wt% sodium carboxymethyl cellulose (CMC) as a binder, add 2wt% acetylene black as a conductive agent, and add an appropriate amount of deionized water to form a uniform slurry; coat the slurry on a copper foil current collector with a thickness of 100μm, then vacuum dry at 80°C for 12 hours, hot press at 120°C, and cut to form a negative electrode sheet;

[0110] Nickel cobalt manganese oxide (NCM523) was selected as the positive electrode active material; NCM523, Ketjen black and PVDF were mixed in a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a dispersant, and stirred evenly to form a slurry; the slurry was evenly coated on an aluminum foil current collector with a thickness of 80 μm, and then vacuum dried at 80°C for 12 hours, hot pressed at 140°C, and cut to form a positive electrode sheet;

[0111] Electrolyte: 1M LiPF6 dissolved in a mixed solution of EC / DMC / EMC (volume ratio 1:1:1) was used as the electrolyte, and 2wt% fluoroethylene carbonate (FEC) was added as an additive;

[0112] The diaphragm is a three-layer composite diaphragm of polypropylene (PP) / polyethylene (PE) / polypropylene (PP), with a thickness of 25 μm and a porosity of 40%.

[0113] The positive electrode, negative electrode, electrolyte and separator were assembled into a battery. The obtained battery performance was tested, and the test results are shown in Table 2.

[0114] Table 2 Performance of batteries prepared using mesoporous carbon materials in the embodiments of the present invention and comparative examples

[0115]

[0116] It can be seen from the above-mentioned Examples 1-12 that the lithium-ion battery prepared by the mesoporous carbon material prepared by the technical solution of the present invention has a better first-charge capacity, first-charge efficiency and capacity retention rate. The mesoporous carbon materials of Comparative Examples 1-3 did not use ZIF-8, SDS and NaCl respectively during the preparation process. Compared with Example 1, the first-charge capacity, first-charge efficiency and capacity retention rate of the batteries of Comparative Examples 1-3 were all reduced. This shows that the mesoporous carbon material obtained by the preparation method of the present invention in coordination with surfactants, inorganic salts and MOFs materials has a more excellent multi-level pore feature. This multi-level pore feature is not only conducive to the uniform distribution and fixation of silicon nanoparticles, but also can provide a large number of lithium ion storage sites, thereby significantly providing the cycle performance and rate performance of lithium-ion batteries. In the preparation method of Comparative Example 4, the polymer material PVP is not used, and the corresponding battery performance decreases. This may be because MOFs cannot be wrapped by PVP, and the micropores formed during the carbonization process tend to be evenly formed on the macropore walls, and do not have the characteristics of being concentrated inside the carbon material. In the preparation process of Comparative Example 5, the slurry is not pretreated, and the corresponding battery performance decreases. This may be because ZIF-8 cannot be effectively cross-linked with the carbon precursor and the polymer material without pretreatment, which is not conducive to the formation of a stable three-dimensional network structure, thereby resulting in a decrease in the stability of the obtained mesoporous carbon material.

[0117] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0118] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0119] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A mesoporous carbon material, characterized in that: The mesoporous carbon material has a multi-level pore structure, which includes macropores with a pore size greater than 50 nm, mesopores with a pore size of 2 to 50 nm, and micropores with a pore size less than 2 nm. The macropores, mesopores, and micropores are interconnected to form a three-dimensional network structure. The mesopores and micropores are distributed on the pore walls of the macropores, the mesopores accounting for more than 70% of the total number of mesopores are distributed in the first region of the mesoporous carbon material, and the micropores accounting for more than 80% of the total number of micropores are distributed in the second region of the mesoporous carbon material, and the first region wraps the second region.

2. The mesoporous carbon material according to claim 1, characterized in that: The total pore volume of all pores in the mesoporous carbon material is 1.5 to 3.0 cm 3 / g, wherein the ratio of the total pore volume of all macropores, the total pore volume of all mesopores and the total pore volume of all micropores is (1-4):(4-7):(2-3); And / or, the specific surface area of ​​the mesoporous carbon material is 1500-2500m 2 / g; And / or, the mesoporous carbon material is doped with 1 to 5 wt% of nitrogen; And / or, the diameter of the mesoporous carbon material is 5 to 20 μm, the first region is a region 0 to 1.5 μm away from the surface of the mesoporous carbon material, and the second region is a region greater than 1.5 μm away from the surface of the mesoporous carbon material; And / or, the multi-level pore structure has a honeycomb structure, and the honeycomb structure includes regularly arranged hexagonal holes.

3. A method for preparing a mesoporous carbon material, characterized in that: include: Under inert atmosphere conditions, pre-treating a mixed slurry containing a carbon precursor, MOFs, a surfactant, an inorganic salt and a polymer material at 120-150° C. to crystallize the MOFs in the mixed slurry and cross-link the MOFs with the carbon precursor and the polymer material; subjecting the pretreated mixed slurry to an in-situ carbonization reaction to obtain an intermediate material; The intermediate material is spray-dried to obtain a mesoporous carbon material.

4. The preparation method according to claim 3, characterized in that: The in-situ carbonization reaction specifically includes: under inert atmosphere conditions, at a heating rate of 2-5°C / min, firstly heating the temperature to 300-500°C and keeping the temperature for 1-2 hours, then heating the temperature to 500-700°C and keeping the temperature for 1-2 hours, and then heating the temperature to 700-1000°C and keeping the temperature for 2-4 hours; And / or, the inlet temperature of the spray drying is 180-300°C, the middle section temperature is 120-200°C, the outlet temperature is 60-100°C, and the spray drying time is 30-120 min; And / or, the pretreatment time is 2 to 4 hours.

5. The preparation method according to claim 3, characterized in that: The content of MOFs in the mixed slurry is 2-10wt% of the carbon precursor, the content of surfactant is 1-5wt% of the carbon precursor, the content of inorganic salt is 5-20wt% of the carbon precursor, and the content of polymer material is 10-30wt% of the carbon precursor; And / or, the polymer material includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylic acid, polystyrene, polymethyl methacrylate, polyethylene glycol, polyvinyl pyridine, polyacrylonitrile, polyamide, polyethylene, polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethyleneimine, polysulfone, polyethersulfone, polylactic acid, polycaprolactone, chitosan, cellulose and its derivatives or polyethylene oxide; And / or, the MOFs include one or a combination of ZIF-8, MOF-5, MIL-88B or HKUST-1; And / or, the carbon precursor includes one or a combination of carbon black, graphene, carbon nanotubes, activated carbon or mesocarbon microspheres; and / or, the surfactant comprises sodium lauryl sulfate; And / or, the inorganic salt comprises sodium chloride.

6. The preparation method according to claim 5, characterized in that: The carbon precursor comprises 20-40 wt% of carbon black, 10-30 wt% of graphene, 5-15 wt% of carbon nanotubes, 10-30 wt% of activated carbon and 5-25 wt% of mesophase carbon microspheres.

7. The preparation method according to claim 3, characterized in that: Also includes: A nitrogen-containing atmosphere is introduced during the in-situ carbonization reaction to nitrogen-dope the mesoporous carbon material.

8. A mesoporous carbon material, characterized in that: The method is prepared by the method described in any one of claims 3 to 7.

9. Use of the mesoporous carbon material according to claim 1, 2 or 8 in energy storage, preparation of catalysts or preparation of adsorbents.

10. The use according to claim 9, characterized in that: The energy storage includes preparing a silicon-carbon composite material for a lithium-ion battery, a lithium-ion battery negative electrode or a lithium-ion battery.